We can be disaster proof a campaign promoting disaster preparedness as a way of life and building a culture of preparedness in the Philippines - Martin, Kyle Miguel Navarro
The Philippines is no stranger to natural disasters, due to our country being located in the Pacific Ring of Fire. Natural disasters is a big problem in our country that gets worse as time goes on, maybe not in the number of deaths and injuries but culturally, people end up panicking when there's a disaster. It's not that people don't know what to do, they know that when there's a disaster you must duck, cover, and hold, go to the nearest evacuation center, prepare a go bag etc., thanks to DepEd and other groups educating these things to people. However, when disaster strikes, people don't apply any of these practices taught and end up doing nothing, running, screaming etc. The poor state of Natural Disaster and Disaster Preparedness in the Philippines can be attributed to the fact that people are unconcern and overlook the practices in their lives. People think that because natural disasters happen rarely, they don't have to prioritize it and focus on the PERSONAL stuff like feeding their family, paying the bills, etc. They are not wrong, these things are very important as well, but Natural Disaster and Disaster Preparedness should be part of that priority, it's rare, but when it attacks, it will leave a big scar in people's lives. Because of the archipelago of the Philippines and the geological studies of natural disasters, people need to prepare because disasters are expected. There are many visuals that tells people what to do during disasters, but the thing about what we have now is that they focus more on commanding people to follow these practices like "do dock, cover, and hold during an earthquake" "prepare a go bag" etc. However, the visuals don't make it PERSONAL for people who know how important disaster preparedness is for their lives. Not only that, there are visuals as well that focuses more on showing how scary disasters are, yes, they will end up following, but people will only follow the practice to avoid the consequences if not followed life if you don't prepare, you'll get injured or die. People will practice for natural disaster out of pressure, but sadly, won't see the values and important of the practice, these values include living longer, less damage, being safe, being able to see your love ones etc. For the visual, it will be an alternative to what we have now, making visuals showing people being calm and confident when encountering a disaster because of their natural preparation, people will hopefully be encouraged to make Disaster Preparedness a Way of Life and make a Culture of Preparedness in the Philippines in the future, as well as to have this mindset not to Prepare because they're Scared but to "Prepare because they Care!"